Can we better predict delayed hemolytic transfusion reactions and hyperhemolysis in sickle cell disease?. (April 2020) - Adkins, Brian D.; Sharma, Deva; Eichbaum, Quentin
Abstract: Delayed hemolytic transfusion reactions (DHTR) occurring in individuals with sickle cell disease (SCD) are usually indolent but may rarely progress to life-threatening hemolysis known as hyperhemolysis syndrome (HHS), which can be difficult to diagnose and manage. We evaluate a predictive model for DHTR proposed by Drs. Pirenne and Yazdanbakhsh. A scoring system and nomogram were utilized in three individuals with SCD and delayed hemolysis, with one likely having HHS. The scoring system is based on identified risk factors for developing hemolysis from patient transfusion history, while the nomogram utilizes persistence of hemoglobin A (HbA) which is not innate to SCD patients. We propose a novel method for HbA estimation to facilitate application of the nomogram. Application of the recently published predictive scoring system revealed a low risk of developing DHTR in one patient and an intermediate risk in two patients. As serial HbA values are not routinely assessed, HbA measurements were only available in one of the three patients, though use of the nomogram predicted a high likelihood of DHTR. The recently published predictive score and nomogram yielded mixed results and should be interpreted with caution when predicting the risk of developing DHTR in individuals with SCD. Management of DHTR/HHS continues to be a challenge for transfusion medicine and hematology services standardized methods to facilitate their early diagnosis and treatment are warranted to improve the safety of blood transfusions in individuals with SCD.